Characterization of Tetracyanopyridine (TCNPy)‐Based Magnets: V[TCNPy]2⋅z (CH2Cl2) (Tc=111 K) and V[TCNPy]3⋅z (CH2Cl2) (Tc=90 K). Issue 40 (16th August 2016) - Hao, Jingjun; Davidson, Royce A.; Kareis, Christopher M.; Kavand, Marzieh; van Schooten, Kipp J.; Boehme, Christoph; Wöß, Eva; Knör, Günther; Miller, Joel S.
Abstract: The reaction of 2, 3, 5, 6‐tetracyanopyridine (TCNPy) with V(CO)6 in CH2 Cl2 forms new organic‐based magnets of V[TCNPy] x ⋅ z  (CH2 Cl2 ) ( x =2, 3) composition. Analysis of the IR spectra suggests that the TCNPy is reduced and coordinated to V II sites through the nitriles. V[TCNPy] x order as ferrimagnets with 111 and 90 K T c values for V[TCNPy]2 and V[TCNPy]3, respectively. Their respective remanent magnetizations and coercive fields are 1260 and 250 emuOe mol −1 and 9 and 6 Oe at 5 K, and they exhibit some spin‐glass behavior. Abstract : Tetracyanopyridine (TCNPy)‐based magnets of V[TCNPy] x ⋅ z  (CH2 Cl2 ) ( x =2, 3) composition with magnetic ordering temperatures of 111 and 90 K have been synthesized and characterized. V[TCNPy]3 is atypical due to the unusual stoichiometry.